2019
DOI: 10.3389/fnins.2019.00433
|View full text |Cite|
|
Sign up to set email alerts
|

Cerebral Autoregulation Evidenced by Synchronized Low Frequency Oscillations in Blood Pressure and Resting-State fMRI

Abstract: Resting-state functional magnetic resonance imaging (rs-fMRI) is a widely used technique for mapping the brain’s functional architecture, so delineating the main sources of variance comprising the signal is crucial. Low frequency oscillations (LFO) that are not of neural origin, but which are driven by mechanisms related to cerebral autoregulation (CA), are present in the blood-oxygenation-level-dependent (BOLD) signal within the rs-fMRI frequency band. In this study we use a MR compatible device (Caretaker, B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
56
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(62 citation statements)
references
References 71 publications
5
56
1
Order By: Relevance
“…Midazolam only significantly changed BP, however spontaneous BP modulations have been shown to predict up to 60% of CBF fluctuations in the middle cerebral artery (Mitsis, Poulin, Robbins, & Marmarelis, ), and substantial transient changes cause spatially widespread modulation of BOLD activation (Harper, Bandler, Spriggs, & Alger, 2000; Kalisch, Elbel, Gössl, Czisch, & Auer, 2001; Wang et al, 2006). While cerebral autoregulatory mechanisms hold CBF constant through arterial blood pressure fluctuations of 50–150 mmHg, delays in these mechanisms can lead to alterations in CBF, confounding the BOLD signal, which may also be correlated with the autoregulatory mechanisms themselves (Kontos et al, ; Lang et al, ; Whittaker, Driver, Venzi, Bright, & Murphy, ). Furthermore, midazolam caused mild, un‐significant decreases in RVT and increases to CO 2, and hypercapnia states have been shown to slow the restoration of CBF (Aaslid, Lindegaard, Sorteberg, & Nornes, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Midazolam only significantly changed BP, however spontaneous BP modulations have been shown to predict up to 60% of CBF fluctuations in the middle cerebral artery (Mitsis, Poulin, Robbins, & Marmarelis, ), and substantial transient changes cause spatially widespread modulation of BOLD activation (Harper, Bandler, Spriggs, & Alger, 2000; Kalisch, Elbel, Gössl, Czisch, & Auer, 2001; Wang et al, 2006). While cerebral autoregulatory mechanisms hold CBF constant through arterial blood pressure fluctuations of 50–150 mmHg, delays in these mechanisms can lead to alterations in CBF, confounding the BOLD signal, which may also be correlated with the autoregulatory mechanisms themselves (Kontos et al, ; Lang et al, ; Whittaker, Driver, Venzi, Bright, & Murphy, ). Furthermore, midazolam caused mild, un‐significant decreases in RVT and increases to CO 2, and hypercapnia states have been shown to slow the restoration of CBF (Aaslid, Lindegaard, Sorteberg, & Nornes, ).…”
Section: Discussionmentioning
confidence: 99%
“…This pattern could represent different noise structures caused by the two drugs; more extensive cleaning on the dataset which modulated fewer physiological parameters (midazolam) removed too much signal to reveal the differences between pre-and postdrug, whereas when more different types of noise were involved (with ketamine) the ratio of removed signal-to-noise was reduced, allowing us to see changes in the remaining signal. Modulations of RVT (Birn et al, 2006), HR (Shmueli et al, 2007), and CO 2 (Birn et al, 2006) have been shown to cause CBF fluctuations in regions with high blood volume, particularly the occipital and posterior cingulate cortices, potentially indicating that for drugs that significantly alter these variables such as ketamine, the regression of CSF and white matter signals would be inadequate to remove these confounds (Murphy et al, 2013 (Kontos et al, 1978;Lang et al, 1999;Whittaker, Driver, Venzi, Bright, & Murphy, 2019). Furthermore, midazolam caused mild, unsignificant decreases in RVT and increases to CO 2, and hypercapnia states have been shown to slow the restoration of CBF (Aaslid, Lindegaard, Sorteberg, & Nornes, 1989).…”
Section: Ketaminementioning
confidence: 99%
“…This limits our possibilities for an accurate pressure and flow phase shift analysis, along with a difference between the cerebral and the brachiocephalic pulse pressure . We have presented a method to estimate arterial compliance, and that accuracy can be improved by noninvasive blood pressure measurements performed simultaneously inside the MR scanner . The two‐element Windkessel model is a basic approximation, where three‐ and four elements have extended the model to better represent the full flow waveform.…”
Section: Discussionmentioning
confidence: 99%
“…Low frequency oscillations of several physiological variables of the cardio-vascular system is a well-known phenomenon and it is thought to be driven by mechanisms related to cerebral autoregulation. 27 However, low frequency data collection of physiologic monitoring signals may not accurately reflect the variability and complexity of these signals or the patient's clinical state. 28 The NeoDoppler system has a high temporal resolution (frame rate 300/s), and data sampling can be synchronized with, for example, cardiac measurements and blood pressure.…”
Section: New Features Obtained With Neodopplermentioning
confidence: 99%